Pengaruh Struktur Modal, Ukuran Perusahaan, Likuiditas dan Perputaran Modal Kerja Terhadap Profitabilitas - Rudi Setiawan (COMPETITIVE, 2022)
This study was conducted to analyze the effect of capital structure, firm size, liquidity and working capital turnover on the profitability of Construction Sector Companies and the 2015-2019 research period. Capital structure is measured by DER, firm size is measured by Company Size, measured by Current Ratio, working capital turnover is measured by WCTO and profitability is measured by ROA. This type of research is quantitative research with a descriptive approach. The sample used is 8 companies with a sampling technique using purposive sampling method. Data analysis in this study used multiple linear regression analysis and hypothesis testing with the help of SPSS 25 program. The results showed that there was a simultaneous significant effect between capital structure, firm size, liquidity and working capital turnover on profitability while partially there was no significant effect.Keywords: Capital Structure, Company Size, Liquidity, Working Capital Turnover, Profitability